Email correspondence - Ana Tolentino::::::; Kathy Meadows::::::; Lacy Serros:::::: (2005)
An email correspondence that includes: Ana Tolentino assisting help with her translations to Lacy Serros. Lacy Serros is Michele Serros cousin and includes her in the correspondance. The dates range from 11/10-11/11 2005.